Women and law : critical feminist perspectives - Kannabirān, Kalpana (SAGE law)
How should we approach the problem of "women and law"? Should the focus be on women-centred laws and their efficacy? Or should the focus be, instead, on the ways in which the law imagines women and the ways in which women have engaged with the law-spilling beyond fields traditionally associated with the phrase "women and law"? And how does violence figure in all these? Women and Law, a compilation of 11 insightful essays, examines these questions and a range of concerns-domestic violence, employment and labour, anti-discrimination jurisprudence, family laws, access to forest and land rights, the right to health, the complexities in the intersection of women's rights with disability rights and women's experiences of repressive legislation such as TADA. This volume attempts at a fresh mapping of the field of women and law from an interdisciplinary perspective and presents the work of activists, lawyers and scholars in conversation.